PENGARUH METODE PROYEK HIDROPONIK TERHADAP KEMAMPUAN SAINS ANAK USIA DINI 5–6 TAHUN DI TAMAN KANAK - KANAK AL IRSYAD - Ani Gusri hidayani; Yaswinda (STKIP Subang, 2026)
This study was motivated by the issue that the majority of children at Al Irsyad Kindergarten struggled with science-related skills. This situation arose because the media used in early childhood science activities lacked appeal. The study aimed to determine the impact of hydroponic media on the science skills of 5- and 6-year-old children at Al Irsyad Kindergarten. A quantitative approach using a quasi-experimental design was employed. The population consisted of all 116 students at Al Irsyad Kindergarten, while the sample comprised two classes—Class B3 and Class B1—with 15 children in each. Oral tests were used to collect data. Data analysis involved a t-test, preceded by prerequisite tests for normality and homogeneity. The data were processed using SPSS 25 for Windows. The analysis revealed that the experimental group's average pre-test score was 11.6667 and the post-test score was 16.5333. For the control group, the average pre-test score was 11.0667 and the post-test score was 15.8000. The final dataset was found to be homogeneous and normally distributed. Hypothesis testing yielded a sig. (2-tailed) value of 0.000 (less than 0.05); therefore, it can be concluded that hydroponic media has an effect on the science skills of children at Al Irsyad Kindergarten.